1979
DOI: 10.1002/pssa.2210530204
|View full text |Cite
|
Sign up to set email alerts
|

Modulated structures and position of the coherent spinodal curve in Al–Zn(22 at%)–Cu(x) alloys

Abstract: The character of the coarsening of modulations in dependence on quenching temperature Ta is studied in Al–Zn(22)–Cu(0 to 3) alloys using X‐ray small angle scattering and TEM measurements (TEM micrographs and diffraction patterns) in the temperature (Ta) range from 70 to 240 °C (XSAS) and 70 to 180 °C (TEM), respectively. The temperature of the coherent spinodal curve is estimated in the range between (230 ± 10) °C. This value agrees fairly well with the results of other authors. The TEM observations of structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…1 the course of TlIfl versus T , obtained for the A1-21.5 at% Zn alloy is shown. From the extrapolation of the straight line of the TIIf1-T plot occurring above Trhn the position of the coherent spinodal curve Tcohsp is evaluated t o be situated a t about (220 f 10) "C. This value is not far from those determined by other authors for this alloy, namely Tcohsp = (230 f 10) "C, by means of the analysis of the wavelength of the spinodal structure in dependence on T , when approaching Fcohsp from lower T , performed by SAXS [16] and TEM investigations [16, 181 or evaluated from the SAXS results obtained below 100 "C [17].…”
Section: Experimental Results and Their Analysismentioning
confidence: 83%
See 1 more Smart Citation
“…1 the course of TlIfl versus T , obtained for the A1-21.5 at% Zn alloy is shown. From the extrapolation of the straight line of the TIIf1-T plot occurring above Trhn the position of the coherent spinodal curve Tcohsp is evaluated t o be situated a t about (220 f 10) "C. This value is not far from those determined by other authors for this alloy, namely Tcohsp = (230 f 10) "C, by means of the analysis of the wavelength of the spinodal structure in dependence on T , when approaching Fcohsp from lower T , performed by SAXS [16] and TEM investigations [16, 181 or evaluated from the SAXS results obtained below 100 "C [17].…”
Section: Experimental Results and Their Analysismentioning
confidence: 83%
“…From these results it can be concluded that the information about the position of Teohsp gained by means of our method fits fairly well the data obtained by other authors. Furthermore, the results presented in [12] and [17] are additionally drawn (see the dashed and the dash-dotted line, respectively) as well as experimentally determined points taken from other authors (full circle [16], square [17], and empty circles [18 to 201). The meaning of the full triangle is explained in the inset of Fig.…”
Section: Experimental Results and Their Analysismentioning
confidence: 99%
“…Such quantitative experiments were not applied to investigate Al-Zn alloys in the vicinity of the coherent spinodal till 1977. The main reason could be that a t elevated temperatures the decomposition processes are remarkably accelerated and that in [27], and Dutkiewicz et al [28] tried to find information on the position of the coherent spinodal by means of SAXS 125 to 281 and TEM investigations 127, 281. Their procedure is based on the idea that the time evolution of the spinodal structure comprising GP zones in their later stage of coarsening may provide reliable information on the mechanism initiating the decomposition of the alloy.…”
Section: Reliable Criteria For Spinodally Decomposing Al-zn Alloysmentioning
confidence: 99%